Increasing Revisit Intention through Visitor Satisfaction to the Indonesian National Museum - Kurniawan Widiyasa, I Gede Bayu; Tuti, Meylani (JDM (Jurnal Dinamika Manajemen), 2023)
This study aims to determine the effect of destination image, visitor experience, and visitor engagement on visit intention through visitor satisfaction. The population in this study were visitors to the National Museum. The sampling technique used was purposive sampling with 148 respondents. The data analysis method uses a structural equation model with the help of smartPLS software. The results of the study show that there is a significant effect of destination image on visitor satisfaction, visitor engagement on visitor satisfaction and visitor experience on visit intention. Meanwhile, the results also show that there is no effect of destination image on visit intention, visitor satisfaction on visit intention and visitor experience on visitor satisfaction. The addition of the customer engagement and customer satisfaction variables to the model is originality in this study in measuring the desire of visitors to return with moderation of customer satisfaction. The managerial implication of this research is that the management of the national museum should increase activities that can enhance the image of the museum among the public as a tourist destination which, in addition to providing education, also provides pleasure, especially for the younger generation to prefer museums.